THE POTENTIAL OF ECONOMIC LOSS DUE TO STUNTING IN INDONESIA - Suryana, Esty Asriyana (UI Scholars Hub, 2023)
Stunting cases continue to increase, along with the high risk of undernutrition, the increasing prevalence of malnutrition, and decreasing productivity. If this condition is not handled correctly, it can affect Indonesia's development performance, inequality, and poverty. Stunting can hinder economic growth and labor productivity, affecting 11% of GDP (gross domestic product) and reducing the income of adult workers by up to 20%. Based on this, it is necessary to make prevention and control efforts in nutrition intervention activities an economic investment. Therefore, this study estimates the economic potential lost due to stunting in children under five. This descriptive study is based on processing secondary data from various related agencies. We employed Konig's formula and correction factors from Horton's study. The results of this study show that the incidence of stunting in children under five in Indonesia in 2021 was 24.4%. Nationally, Indonesia has the potential for economic loss due to stunting in toddlers, which ranges from IDR 15,062 to IDR 67,780 billion. These are equivalent to a range of 0.89-3.99% of the total GDP in 2021 (IDR 16,970.8 trillion).